Against the Death Penalty : Writings from the First Abolitionists-Giuseppe Pelli and Cesare Beccaria - Garnsey, Peter; Beccaria, Cesare, marchese di, 1738-1794; Pelli Bencivenni, Giuseppe, 1729-1808 (Book collections on Project MUSE., 2020)
"The Italian political and legal thinker Cesare Beccaria (1738-1794) is justly regarded as the founding father of the movement for criminal law reform that emerged in Europe in the mid-18th century. His treatise, On Crimes and Punishments (1764), is a seminal text that has had an enormous and lasting influence on politicians, jurists, philosophers and theologians. In particular, his attack on the death penalty has dominated the historical and philosophical debate. However, an earlier treatise that specifically argues for the abolition of the death penalty has recently come to light. This is Contro la pena di morte (1761), by Giuseppe Pelli (1729-1808). Pelli and Beccaria were not in contact and apparently had no knowledge of the other's work until Beccaria's treatise appeared. Pelli's treatise was never completed and remained unpublished for 250 years. It was discovered in the late 1980's among the papers of the descendants of his adopted daughter, and was published in Italian in 2014. In Against the Death Penalty, Peter Garnsey, a historian of the Roman Empire and Italy, provides the first English translation of this important yet forgotten text. Although Beccaria attacked the whole criminal justice system of his time, Pelli's work was singulr in its focus on attacking on just the death penalty. As such, it was the first attack of any substance that appeared in Europe, and although unfinished, it is a work of considerable sophistication and depth. It is a comprehensive critique, considerably longer and more thorough than that of Beccaria. Pelli was also a man of religious convictions and operated within the Catholic tradition: for his key arguments he drew on the writings of the natural jurists, in particular Grotius and Pufendorf. Garnsey provides a substantial introduction, the bulk of which is a comparative evaluation of the discussions of Pelli and Beccaria on the death penalty and alternative punishments. He also provides historical context for the intellectual and social environment in which the two men lived and from which their works emerged. Although much has been written about Beccarria, little is known or has been written about Pelli's life. Garnsey reconstructs what is important for understanding his text by drawing on the massive diary Pelli left,which has also only recently become available. It not only sheds light on Pelli's intellectual development but provides a fascinating, extraordinarily informative, and revealing day-by-day, profoundly personal account of a man of letters who became a bureaucrat in the service of the Habsburg Monarchy"--